Seguridad y hospitalidad y su incidencia en el turismo del cantón Quevedo, año 2021 - Santillán Luna, Karelys Maryan (2021)
The proposed research deals with the issue of security and hospitality and its incidence in the tourism of the Quevedo canton, year 2021, applying the survey technique, it was possible to identify the main drawbacks in the tourism sector, determined that the lack of control and planning Regarding the control of crime, it has had a negative influence on tourism because through this modality, every day the number of people who are victims of assaults, scams, extortions grows, which has generated a bad image for the canton, where Tourists prefer other destinations that provide them with greater security, another problem that was found that there is no tourist information, where visitors are informed about the areas of the Quevedo environment that are safe to visit, tourists who arrive in Quevedo go to certain sites Although they are tourist attractions, it is preferable to go in groups, protecting each other's safety, avoiding being one of the victims. ace of crime that operates in the city. Without a doubt, Quevedo has beautiful natural environments, tradition and culture where various tourist activities can be carried out, it is necessary that this potential be taken advantage of by raising bills where citizen security is attended as an emergency, also include training for merchants to provide an efficient and hospitable service to tourists and they will come back again